2017
DOI: 10.1101/mcs.a001727
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation reveals the novel missense V419L variant in TGFBR2 associated with Loeys–Dietz syndrome (LDS) impairs canonical TGF-β signaling

Abstract: TGF-β-related heritable connective tissue disorders are characterized by a similar pattern of cardiovascular defects, including aortic root dilatation, mitral valve prolapse, vascular aneurysms, and vascular dissections and exhibit incomplete penetrance and variable expressivity. Because of the phenotypic overlap of these disorders, panel-based genetic testing is frequently used to confirm the clinical findings. Unfortunately in many cases, variants of uncertain significance (VUSs) obscure the genetic diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…To test the utility of our biophysically parametrized structural bioinformatic methods [ 1 4 ], we selected KDM6A variants within the catalytic domain found in patients with a Kabuki syndrome diagnosis. These have previously predicted to be damaging in most cases (with a few exceptions) by available impact predictors but for which more studies remain necessary to determine if their classification is valid and to identify the mechanisms underlying their dysfunction (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the utility of our biophysically parametrized structural bioinformatic methods [ 1 4 ], we selected KDM6A variants within the catalytic domain found in patients with a Kabuki syndrome diagnosis. These have previously predicted to be damaging in most cases (with a few exceptions) by available impact predictors but for which more studies remain necessary to determine if their classification is valid and to identify the mechanisms underlying their dysfunction (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our studies are focused on the use and optimization of structural bioinformatics methods for improving the interpretation of data derived from next generation sequencing in cases presenting with rare diseases [ 1 4 ]. Extensive studies in our laboratories have previously demonstrated that these approaches yield not only information on the damaging effects of likely pathogenic variants but also yield useful mechanistic information on their pathophysiological impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous variants about TGFBR2 mutant reported in ClinVar showed that 86 of the 87 plausible pathogenic missense variants are located in the kinase domain. Study showed that p.Val419Leu variant in the TGFBR2 affected the receptor function through alteration of its structure and inactivation of kinase conformations (Cousin et al, 2017). In this study, we discovered that the c.1613T > C/p.Val538Ala variant also located in the kinase domain of TGFBR2 protein, and the overall scaffold of the mutated structure is similar to the native one by MD stimulation.…”
Section: Pp3mentioning
confidence: 63%
“…); ACMG, American College of Medical Genetics and Genomics; AMP, Association for Molecular Pathology. Cousin et al, 2017). Since the c.1613T > C/p.Val538Ala variant of TGFBR2 was reported as a likely pathogenic variant in 2016 (Luo et al, 2016), these cellular results confirmed the pathogenicity of this variant.…”
Section: Pp3mentioning
confidence: 97%
See 1 more Smart Citation